Controlling of semiconductor/metal junction barrier by 5,10,15,20-tetraphenyl-21H,23H-porphine ruthenium(II) carbonyl - Yakuphanoğlu, Fahrettin (Natl Inst Optoelectronics, 2007)
The electrical characteristics of RuP/p-Si/Al junction barrier have been investigated by current-voltage and capacitance-voltage characteristics. A deviation in I-V characteristic of the diode is observed due to effect of series resistance and interfacial layer. RuP/p-Si/Al diode is a metal-interfacial layer-semiconductor type diode with calculated electronic parameters (ideality factor, series resistance and barrier height-, n=1.95, R-s=6.25 k Omega and phi(B)=1.23 eV). The obtained barrier height and ideality factor values of RuP/p-Si/Al diode at the room temperature is significantly larger that that for the conventional Al/p-Si Schottky diode. It is evaluated that RuP organic layer modifies electronic properties of metalsemiconductor devices based on p-Si.
Keywords: metal-semiconductor contact; organic semiconductor; series resistance